2021
DOI: 10.3892/etm.2021.10005
|View full text |Cite
|
Sign up to set email alerts
|

The herbal agent plantamajoside, exerts a potential inhibitory effect on the development of hepatocellular carcinoma

Abstract: Plantamajoside (PMS), a major component of Plantago asiatica L , has several pharmacological properties, including anti-proliferative, anti-inflammatory and anti-tumor effects. However, the effects of PMS on hepatocellular carcinoma (HCC) have yet to be determined. The aim of the present study was to investigate the effects of PMS on HCC and elucidate the underlying mechanism. All assays were conducted using 5 groups, namely control, sorafenib, and PMS 100, 50, and 25 µg/ml groups. Cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Plantamajoside showed inhibitory activity on the viability of human cancer cells in the following cell lines: breast MDA-MB-231 [ 46 ], hepatocellular carcinoma Huh7 [ 47 , 48 ], PLC/PRF 5, THLE-2 [ 47 ] and HepG2 [ 48 , 49 , 50 ], cervical SiHa and CaSki [ 51 ], esophageal Eca-109 and TE-1 [ 52 ], and malignant melanoma A2058 [ 53 ]. Comparisons with our results are difficult since IC 50 values were not reported in those investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Plantamajoside showed inhibitory activity on the viability of human cancer cells in the following cell lines: breast MDA-MB-231 [ 46 ], hepatocellular carcinoma Huh7 [ 47 , 48 ], PLC/PRF 5, THLE-2 [ 47 ] and HepG2 [ 48 , 49 , 50 ], cervical SiHa and CaSki [ 51 ], esophageal Eca-109 and TE-1 [ 52 ], and malignant melanoma A2058 [ 53 ]. Comparisons with our results are difficult since IC 50 values were not reported in those investigations.…”
Section: Discussionmentioning
confidence: 99%
“…Phenolics such as chlorogenic acid, gallic acid, caffeic acid, and rosmarinic acid are secondary metabolites in plants . Because of their antioxidant and anti-inflammatory properties, they can be used as active ingredients in the cosmetic, food, and pharmaceutical industries. Table presents the newest findings in the bioactivities and possible future applications of the chosen phenolic compounds extracted from plants. Based on the information presented in Table , it is clear that current research focuses mostly on the medical application of phenolics in anticancer preparations. It is worth mentioning that phenolics have shown activities in the treatment of other civilization and neurodegenerative diseases.…”
Section: The Most Interesting Bioactive Compounds Extracted With Dess...mentioning
confidence: 99%
“…Additionally, studies have reported that phenylpropanoid (chlorogenic acid and 16-O-caffeoyl-16-hydroxylhexadecanoic acid) and quinone (thymoquinone and juglanthraquinone C) induce apoptosis in HCC cell lines[ 45 - 48 ]. Separate studies have demonstrated that 4-acetylantrocamol LT3 induces autophagy by activation of the AMPK pathway[ 49 ], while aloin and andrographolide induce apoptosis[ 50 , 51 ], and plantamajoside and sanguisorba Officinalis L. decrease proliferation in HCC cell lines[ 52 , 53 ]. Curcumin also offers antioxidant, apoptotic, and anti-inflammatory effects, and is thus applied in the treatment of HCC[ 54 ].…”
Section: Augmented Local Controlmentioning
confidence: 99%